Occupational Hazards and Environmental Consequences of Sandstone Mining: A Case Study from Soorsagar, Jodhpur, Rajasthan - Saha, Bikas (The Nucleus, 2025)
Mining plays a crucial role in the economic growth and supports national development. However, it also raises significant concerns due to its environmental impact and health risks, particularly in the nearby areas. In India’s sandstone mines, both mechanical and manual methods are employed. Mining operations rely heavily on equipment such as trucks, dumpers, compressors, drills for blasting, and cranes for lifting heavy blocks. These activities generate large amounts of dust containing high levels of silica, which poses severe health risks. Prolonged inhalation of silica dust can lead to silicosis, a preventable but serious disease characterized by dyspnoea (shortness of breath) and persistent cough, and is sometimes associated with lung cancer and tuberculosis. Silicosis is one of the most common occupational diseases globally and has a significant impact on workers’ health in developing countries like India. The use of heavy machinery and vehicles also creates high levels of noise and vibration in the surrounding. Prolonged exposure to noise can result in occupational hearing loss due to neurosensory deafness. Additionally, continuous exposure to whole-body vibrations leads to degenerative spinal conditions, including chronic back pain. Although stone quarrying near Soorsagar, Jodhpur, contributes to both the rural and national economies, its environmental consequences are considerable. Unplanned and haphazard quarrying has resulted in environmental degradation, and unauthorized mining activities have further worsened the local ecological balance.